2017
DOI: 10.1158/1535-7163.mct-16-0767
|View full text |Cite
|
Sign up to set email alerts
|

The DNA-Binding Polyamine Moiety in the Vectorized DNA Topoisomerase II Inhibitor F14512 Alters Reparability of the Consequent Enzyme-Linked DNA Double-Strand Breaks

Abstract: Poisons of topoisomerase II (TOP2) kill cancer cells by preventing religation of intermediate DNA breaks during the enzymatic process and thus by accumulating enzyme-drug-DNA complexes called TOP2 cleavage-complex (TOP2cc). F14512 is a highly cytotoxic polyamine-vectorized TOP2 inhibitor derived from etoposide and currently in clinical trials. It was shown that F14512 has acquired DNA-binding properties and that the stability of TOP2cc was strongly increased. Paradoxically, at equitoxic concentrations in cells… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 48 publications
0
11
0
Order By: Relevance
“…In parallel, using the same genetic approach, we isolated F14R HAP1clones resistant to a lethal concentration of 30 nM F14512, a potent and selective TOP2A poison (49). Targeted sequencing of TOP2A cDNA in seven F14R clones revealed TOP2A mutations for five of them, confirming that TOP2A is the main mediator of F14512 cytotoxicity.…”
Section: Top2a Mutations Confer Resistance To Clastogenic G4 Ligands mentioning
confidence: 82%
See 1 more Smart Citation
“…In parallel, using the same genetic approach, we isolated F14R HAP1clones resistant to a lethal concentration of 30 nM F14512, a potent and selective TOP2A poison (49). Targeted sequencing of TOP2A cDNA in seven F14R clones revealed TOP2A mutations for five of them, confirming that TOP2A is the main mediator of F14512 cytotoxicity.…”
Section: Top2a Mutations Confer Resistance To Clastogenic G4 Ligands mentioning
confidence: 82%
“…Clonogenic assay was performed as described by (49). Briefly, after transfection with siRNA, HeLa cells were seeded at low density (250 cells/well) the day before treatment, pre-incubated with 5,6-dichloro-1-beta-D-ribofuranosylbenzimidazole (DRB) or dimethylsulfoxide (DMSO)…”
Section: Clonogenic Assaymentioning
confidence: 99%
“…The presence of a spermine moiety in the compound molecule led to an increase in the degree of DNA binding and consequently to an enhancement of the inhibition of Top II activity 143 . Moreover, the overexpression of polyamine transport system observed in cancer tumours was used to intensify selective drug uptake by cancer cells 144,145 . In vitro activity of F14512 was evaluated in 29 human cancer cell lines (i.a.…”
Section: Clinically Important Epipodophyllotoxinsmentioning
confidence: 99%
“…19, 23 In contrast, at least in A549 lung cancer cells, it has been suggested that topoisomerase IIα is the primary cytotoxic target of the drug. 27 However, the level of topoisomerase IIα in the A549 cells used in the study was considerably higher than that of topoisomerase IIβ. 27 Consequently, the relative roles of the two enzyme isoforms in the actions of F14512 in lung and other cancer cells remain an open question.…”
mentioning
confidence: 80%